O movimento do significado de grupos de apoio na cadeia criativa de atividades no programa Ação Cidadã - Fuga, Valdite Pereira (2009)
This research is inserted in Applied Linguistic field and aims at investigating The movement of the meaning of Teacher Support Team in the Creative Chain of Activities in the Acting as Citizen Program, specifically, in the project entitled Reading in Different Areas (LDA), developed by the Language in Activities at School Contexts (LACE) Research Group, on Education and Language Area from Catholic University of São Paulo, SP. The theoretical framework of this study comprehends the Marxist-dialectical (Marx, 1883/1890/2007) and Spinozinan monist philosophical perspective (Spinoza, 1667/2003) to discuss the concept of totality, which is underlying the Creative Chain of Activities concept (Liberali, 2006). This framework also converges on Socio-Historical-Cultural Activity Theory (TASHC) (Vygotsky and partners, 1934), which, in this study, enhances the importance of apprenticeship through activities and interactions in the researched context. Language is seen under the Bakhtinian Circle s perspective (1975/1995) which, in here, emphasizes the events of human existence through interactions in the several LDA contexts; this was supported by Teacher Support Team (TST) (Daniels and partners, 2004) as a teacher organization in order to develop the work that was carried out in the schools belonging to Carapicuíba Regional Division. This study is guided by the Critical Collaborative Intervention Research aspects (Magalhães, 2002, 2004, 2006, 2009), understood as a process of participation in the construction of knowledge, which emphasizes the role of collaboration as an essential issue for the development of all of those involved in the process. To discuss the outcomes, it brings out Bronckart s linguistic-discoursive categories (1997/1999) (implication/autonomy aspects, modalization, prototypic sequences), as well as the interpretation grounded on this theoretical framework. The results indicate that TST praxis is based on collaborative aspects. TST acted as a protagonist in their contexts; was creative and brought their jargons to the LDA s context.. TST s development of meaning followed the dialectic movement, according to Marx s theory (1883/1890/2007); it presents a new way of organization and work in LDA s, which is different from the British proposal